Correction: Environmental Transmission of Typhoid Fever in an Urban Slum. - PLOS Neglected Tropical Diseases Staff (PLOS Neglected Tropical Diseases, 2016)
[This corrects the article DOI:10.1371/journal.pntd.0004212.].